The Hindenburg Disaster, 1937 - Tarshis, Lauren; Dawson, Scott (New York : Scholastic, 2016)
"For eleven year-old Hugo Ballard, flying on the Hindenburg is a dream come true. Hugo, his parents, and his four-year-old sister Gertie are making the thrilling four-thousand-mile journey across the Atlantic in a zeppelin as big as the Titanic. But as the zeppelin gets ready to land, a blast rocks the Hindenburg and fire consumes the ship. The entire disaster lasts a mere thirty-two seconds, but in those few seconds, Hugo finds himself separated from his family and in a desperate race to escape the flames. The Hindenburg is doomed. And so, it seems, is Hugo. Will he survive this historic disaster?"--Dust jacket flap.
Includes filmography and bibliographical references (pages 105-108).
Keywords: Hindenburg (Airship) -- Juvenile fiction; Hindenburg (Airship) -- Fiction; Aircraft accidents -- Juvenile fiction; Airships -- Juvenile fiction; Survival -- Juvenile fiction; Aircraft accidents -- Fiction; Airships -- Fiction; Survival -- Fiction